Modelagem, controle e gerenciamento da operação de microrredes com fontes renováveis - Almada, Janaína Barbosa (2013)
Nowadays, the distribution networks of electricity are the segment of the electrical power systems that has experienced more changes, due in particular to the presence of distributed generation and the technological advances in the areas of instrumentation, automation, measurement, information technology and comunication. This work aims to present the modelling, the control and the operation management of a group of small-scale energy resources connected to the low voltage, which coordinated form a microgrid. The microgrid energy resources are solar photovoltaic sources, wind energy based on double fed induction generator and hydrogen fuel cell, and a storage system with batteries. Two conceptions are developed: a single-phase microgrid and a three-phase microgrid, both operating in connected mode and isolated from the utility. Each energy resource is connected to a point of common coupling through power converters. For each converter was designed a set of control loops. The master-slave strategy was used to control the converters and to microgrid management. In master-slave configuration only the master converter is designed to be the voltage reference and others operate as a current source. For managing the steady state operation of microgrids different operating scenarios were considered, with variation of load and generation levels, as well as changes in tariff flags, for load supply with economy and sources operating at maximum efficiency. The proposed systems operate satisfactorily fulfill the requirements of utility for synchronization and disconnection. The injected currents are below the allowed distortion level. In stand-alone mode, the system voltage remains within the appropriate level of amplitude and frequency.